OBSERVATIONS ON THE INTRAOVARIAN OVA OF A FEW TACHYSURIDS FROM INDIAN WATERS - Menon, N Gopinatha (Indian Journal of Fisheries, 2011)
Three different groups of intraovarian ova, ’a’, ’b’ and ’c’, are noticed in the ovary of mouthbrooding tachysurid catfishes; the former two groups are small nonyolked and reproductively nonfunctional and the last group is yolked, opaque and functional. The group ’a’ and ’b’ ova are sequentially arranged, respectively in the oviducal and posterior region while the group ’c’ ova occupies the anterior three-fourth of the ovarian cavity. There is a certain ratio in the number of ova of the three groups, probably characteristic of each species. All the nonfunctional ova of the groups ’a’ and ’b’ and ripe functional group ’c’ are spawned in a bunch and taken into the mouth of male, where only the group ’c’ ripe eggs develop into young ones.